Intake of Marine-Derived Omega-3 Polyunsaturated Fatty Acids and Mortality in Renal Transplant Recipients - Gomes Neto, António W. (Nutrients, 2017)
The effect of marine-derived omega-3 polyunsaturated fatty acids (n-3 PUFA) on long-term outcome in renal transplant recipients (RTR) remains unclear. We investigated whether marine-derived n-3 PUFA intake is associated with all-cause and cardiovascular (CV) mortality in RTR. Intake of eicosapentaenoic acid plus docosahexaenoic acid (EPA-DHA) was assessed using a validated Food Frequency Questionnaire. Cox regression analyses were performed to evaluate the associations of EPA-DHA intake with all-cause and CV mortality. We included 627 RTR (age 53 ± 13 years). EPA-DHA intake was 102 (42–215) mg/day. During median follow-up of 5.4 years, 130 (21%) RTR died, with 52 (8.3%) due to CV causes. EPA-DHA intake was associated with lower risk of all-cause mortality (Hazard Ratio (HR) 0.85; 95% confidence interval (95% CI) 0.75–0.97). Age (p = 0.03) and smoking status (p = 0.01) significantly modified this association, with lower risk of all-cause and CV mortality particularly in older (HR 0.75, 95% CI 0.61–0.92; HR 0.68, 95% CI 0.48–0.95) and non-smoking RTR (HR 0.80, 95% CI 0.68–0.93; HR 0.74, 95% CI 0.56–0.98). In conclusion, marine-derived n-3 PUFA intake is inversely associated with risk of all-cause and CV mortality in RTR. The strongest associations were present in subgroups of patients, which adds further evidence to the plea for EPA-DHA supplementation, particularly in elderly and non-smoking RTR.